Roles of Iron Limitation in Phytoplankton Dynamics in the Western and Eastern Subarctic Pacific - Zhang, Hao-Ran; Wang, Yuntao; Xiu, Peng; Qi, Yiquan; Chai, Fei (Frontiers in Marine Science, 2021)
The subarctic Pacific is one of the major high-nitrate, low-chlorophyll (HNLC) regions where the marine productivity is greatly limited by the supply of iron (Fe). There is a distinct seasonal difference in the chlorophyll concentrations of the east and west sides of the subarctic Pacific due to differences in driving mechanisms. In the western subarctic Pacific, two chlorophyll concentration peaks occur: the peak in spring and early summer is dominated by diatoms, while the peak in late summer and autumn is dominated by small phytoplankton. In the eastern subarctic Pacific, a single chlorophyll concentration peak occurs in late summer, and small phytoplankton dominate throughout the year. Here, two 1D physical–biological models with Fe cycles are applied to Ocean Station K2 (Stn. K2) in the western subarctic Pacific and Ocean Station Papa (Stn. Papa) in the eastern subarctic Pacific. The models are used to study the role of Fe limitation in regulating the seasonal differences in phytoplankton populations by reproducing the seasonal variability in ocean properties in each region. The results are reasonably comparable to observational data, i.e., cruise and BGC-Argo data, showing that the difference in bioavailable Fe (BFe) between Stn. K2 and Stn. Papa plays a dominant role in controlling the respective seasonal variabilities of diatom and small phytoplankton growth. At Stn. Papa, there is less BFe, and the Fe limitation of diatom growth is twice as strong as that at Stn. K2; however, the difference in Fe limitation of small phytoplankton growth between these two regions is relatively small. At Stn. K2, the decrease in BFe during summer reduces the growth rate of diatoms, which leads to a rapid reduction in diatom biomass. Simultaneously, the decrease in BFe has little impact on small phytoplankton growth, which helps maintain the relatively high small phytoplankton biomass until autumn. The experiments simulating a further increase in atmospheric Fe deposition show that the responses of phytoplankton primary production in the eastern subarctic Pacific are stronger than those in the western subarctic Pacific but contribute little to primary production, as the Fe limitation of phytoplankton growth would be replaced by macronutrient limitation.